The effect of adding Coping Power Program-Sweden to Parent Management Training-effects and moderators in a randomized controlled trial - Helander, Maria; Lochman, John; Högström, Jens; Ljótsson, Brjánn; Hellner, Clara; Enebrink, Pia (Behaviour research and therapy, 2018)
For children with oppositional defiant disorder (ODD), Parent Management Training (PMT) is a recommended treatment in addition to child Cognitive Behavioral Therapy (child-CBT). There is however a lack of studies investigating the additive effect of group-based child-CBT to PMT for children between 8 and 12 years. The current study investigated the incremental effect of group-based child-CBT, based on the Coping Power Program, when added to the Swedish group-based PMT program KOMET. Outcomes were child behavior problems, child prosocial behavior, parenting skills and the moderating effect of child characteristics. One hundred and twenty children 8–12 years with ODD or Disruptive Behavioral Disorder NOS and their parents were randomized either to combined child-CBT and PMT (n = 63) or to PMT only (n = 57) in Swedish Child- and Adolescent Psychiatric settings. Participants were assessed pre- and post-treatment using semi-structured interviews and child- and parent ratings. After treatment, behavior problems were reduced in both groups. Prosocial behavior were significantly more improved in the combined treatment. Parenting skills were improved in both groups. In moderator analyses, behavior problems and prosocial behavior improved significantly more in the combined treatment compared to PMT only in the group of children with high levels of ODD symptoms. •We investigated the effect of group child CBT and Parent Management Training (PMT) compared to PMT only.•The study population was children between 8–12 years with oppositional defiant disorder and their parents.•PMT by itself is an effective treatment for children with oppositional defiant disorder in order to reduce behavior problems.•Group child CBT combined with PMT improves social skills significantly more than PMT only.•For children with high levels of disruptive behavior, child CBT combined with PMT reduced behavior problems more than PMT only.